Pelatihan Penanganan Limbah Produksi Berbahaya Pada Perusahaan Sablon di Tangerang - Lesmana, Sakti Aji; Triana, Novera Elisa; Beatrix, Meike Elsye; Aprianti, Melani (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
Hazardous and Toxic Waste (B3) from home-based screen printing industries poses a threat to the environment and public health if not properly managed. Low environmental literacy and limited waste management infrastructure in the small and medium industry (SMI) sector remain key challenges. This Community Service Program (PkM) aimed to enhance the knowledge and skills of screen printing practitioners in managing B3 waste through educational and participatory approaches. The program was conducted at PT. Shalom Dunia, Tangerang City, over five months, with the main training held in April 2025. Methods included field observation, interactive training, hands-on practice, group discussions, and emergency response simulations. Evaluation was carried out through questionnaires, pre-tests, and post-tests. Results showed an increase in correct responses from 41% to 92% after the training, and 99% of participants stated that the program significantly improved their awareness of workplace safety and environmental protection. This program proved effective as an ecological education model that can be replicated in other creative industry sectors to support sustainable development.